Genetic susceptibility to schizophrenia: role of dopaminergic pathway gene polymorphisms. (February 2009) - Gupta, Meenal; Chauhan, Chitra; Bhatnagar, Pallav; Gupta, Simone; Grover, Sandeep; Singh, Prashant K; Purushottam, Meera; Mukherjee, Odity; Jain, Sanjeev; Brahmachari, Samir K; Kukreti, Ritushree
Aim: We investigated 16 polymorphisms from three genes, dopamine receptor D2 ( DRD2 ), catechol- O -methyl transferase ( COMT ) and brain derived neurotrophic factor ( BDNF ), which are involved in the dopaminergic pathways, and have been reported to be associated with susceptibility to schizophrenia and response to antipsychotic therapy.Materials & methods: Single-locus association analyses of these polymorphisms were carried out in 254 patients with schizophrenia and 225 controls, all of southern Indian origin. Additionally, multifactor-dimensionality reduction analysis was performed in 422 samples (243 cases and 179 controls) to examine the gene––gene interactions and to identify combinations of multilocus genotypes associated with either high or low risk for the disease.Results: Our results demonstrated initial significant associations of two SNPs for DRD2 (rs11608185, genotype: χχ 2 = 6.29, p-value = 0.043; rs6275, genotype: χχ 2 = 8.91, p-value = 0.011), and one SNP in the COMT gene (rs4680, genotype: χχ 2 = 6.67, p-value = 0.035 and allele: χχ 2 = 4.75, p-value = 0.029; odds ratio: 1.33, 95% confidence interval: 1.02––1.73), but not after correction for multiple comparisons indicating a weak association of individual markers of DRD2 and COMT with schizophrenia. Multifactor-dimensionality reduction analysis suggested a two locus model (rs6275/ DRD2 and rs4680/ COMT ) as the best model for gene––gene interaction with 90% cross-validation consistency and 42.42% prediction error in predicting disease risk among schizophrenia patients.Conclusion: The present study thus emphasizes the need for multigene interaction studies in complex disorders such as schizophrenia and to understand response to drug treatment, which could lead to a targeted and more effective treatment.